ENVIRONMENTAL AND ECONOMIC ASPECTS OF THE USE OF BACTERICIDAL AND FUNGICIDAL FERTILIZERS IN THE TECHNOLOGY OF GROWING SPRING WHEAT (INNOVATIVE ECONOMY, 2026)
Yashchuk T.S., Samets N.P., Dovhan O.M. ENVIRONMENTAL AND ECONOMIC ASPECTS OF THE USE OF BACTERICIDAL AND FUNGICIDAL FERTILIZERS IN THE TECHNOLOGY OF GROWING SPRING WHEATPurpose. The aim of the article is to evaluate the effectiveness of the use of bactericidal and fungicidal fertilizers in shaping the productivity of the spring wheat agrocenosis under the agro climatic influences of the Western Forest-Steppe zone.Methodology of research. The theoretical and methodological basis of the research was specialized and generally accepted methods and techniques used in agronomy. To achieve the set goal, general scientific and special methods were used, such as: induction and deduction – for searching, systematizing and processing the studied information; logical – for generalizing the processed data set; field – for observing the growth and development of plants during the growing season, the formation of yield; laboratory – for determining the qualitative indicators of grain; mathematical and statistical – conducting variance analysis; computational and comparative – for determining yield, economic assessment of the studied elements of technology; tabular and graphical – for a visual presentation of systematized information; abstract and logical and generalization – for forming conclusions and proposals from the conducted research.Findings. The ecological and economic rationality and effectiveness of the use of bactericidal-fungicidal fertilizers to increase the yield of spring wheat and the quality of grain and its resistance to harmful organisms have been substantiated. It has been established that a high level of spring wheat productivity was achieved due to the action of the bactericidal and fungicidal fertilizers Silver Phos and VERNO FG in variants with the treatment of crops during the vegetation period twice in the tillering phase and in the tube phase (+0.44 t/ha and +0.49 t/ha in the best variants). Conditionally, the net profit in these variants was 31539; 31718 UAH/ha, the level of profitability – 153.8; 156.2%. A slight incidence of crops affected by pathogens of pyrenophorosis, septoria and powdery mildew was established, other crop lesions were not noted. The ecological and economic feasibility of integrating bactericidal and fungicidal fertilizers (BFD) into the technology of growing spring wheat as a tool for managing productivity and stress resistance of plants is argued. It is determined that the use of BFD is an important factor in realizing the genetic potential of modern wheat varieties in conditions of unstable moisture, ensuring the transition of grain to a higher quality class by increasing the content of gluten and protein in grain.Originality. The position on the synergistic action of microbial agents and mineral components has been further developed, which allows not only to suppress the development of phytopathogens, but also to increase crop yield: the use of bactericidal and fungicidal fertilizers in the spring wheat nutrition system provided a total yield increase effect of 6.4-7.1%.Practical value. The results of scientific research can be used to implement effective technological elements for managing the productivity of grain crops in the conditions of the Western Forest-Steppe using bactericidal and fungicidal fertilizers, which will contribute to the growth of high-quality grain production and economic feasibility, which is ensured by the return on investment.Key words: cereal crops, spring wheat, yield, bactericidal and fungicidal fertilizers, competitiveness, profitability.
Keywords: cereal crops; spring wheat; yield; bactericidal and fungicidal fertilizers; competitiveness; profitability